The Difference between Male and Female Students’ Attitude toward Cooperative Learning in English Subject of MAN 1 Kampar - Ariani, Rini; Nurdiana, Nurdiana; Afrizal, Afrizal (Indonesian Journal of Integrated English Language Teaching, 2023)
The aim of this research was to find out the difference between male and female students’ attitude toward cooperative learning in English subject of MAN 1 Kampar. There were 30 samples of this research; 15 male and 15 female students. The researcher used quota sampling for the sample technique. The instrument used was the affective, cognitive and behavior aspect of attitude which has 15 statements. The research finding was showed that male students have negative attitude and female students showed positive attitude. In affective category, male students perceived that cooperative learning does not help them to socialize more, contrast with female students. In cognitive aspect, most of male students disagree that cooperative learning environment develop trust toward classmates, individual studying is more enjoyable than working in groups and individual study offers better result but a few female students think individual study is more enjoyable than working in groups and female students show neutral attitude which individual study offers better result. In behavior aspect a few male students agree while studying in cooperation students’ guide each other besides female students have positive attitude toward statement while studying in cooperation, students guide each other. The statistical data analysis finding by using SPSS 28.0 independent sample test revealed that there was a significant different between male and female in learning attitude by calculation that significant two tailed test sig 0.049 p<0.05. Key words: Attitude, Cooperative Learning, Male, Female